Cost variation analysis of various brands of anti-epileptic drugs currently available in Indian pharmaceutical market - Allisabanavar, Saiyadali A.; S., Narayana Reddy (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Epilepsy is a common neurological disorder affecting about 10 million persons in India. The compliance to a particular antiepileptic drug is highly dependent on the cost of the drug which directly translates into success or failure of therapy. Hence there is a need for all clinicians to keep themselves updated with the latest prices and price variation of the commonly prescribed drugs. This study aims to analyze cost variation of various brands of anti-epileptic drugs currently available in Indian pharmaceutical market. Methods: Current Index of Medical Specialities July-October 2016 edition was referred to know the maximum and minimum price in INR of various brands of anti- epileptic drugs in India. Further analysis was done by using Percentage Cost Variation. Results: There is wide variation in the prices of different brands of same antiepileptic agents in Indian market. The highest % cost variation was found for diazepam 5mg tablet (374.42), followed by lorazepam 2mg tablet (213.63), carbamazepine 100mg syrup/5ml-100ml (172.58), levetiracetam 1000mg FC-tablet (168.57), lamotrigine 25mg DIS- tablet (150), clobazam 10mg tablet (147.37), clonazepam 0.5mg tablet (145.90), oxcarbazepine 150mg tablet (89.46), gabapentin 300mg capsule (71.67), valproic acid 200mg FC-tablet (58.62), divalproex sodium 500mg ER-tablet (47.82), topiramate 50mg tablet (41.66) and lowest % cost variation was of phenytoin sodium 300mg tablet (0.23). Conclusions: The average percentage price variation of different brands of same oral anti-epileptic drug in Indian market is very wide. To counter act such cost variation, physicians should be encouraged to prescribe a medication brand with low cost. This in turn reduces the unnecessary economic burden to the patients.